An experimental and simulation study of interface crack on zinc coating/304 stainless steel. (10th February 2018) - Zhang, Hua; Yang, Jian; Hu, Jinlin; Li, Xian; Li, Mingwei; Wang, Chenglong
Graphical abstract: Highlights: An acoustic emission technique was taken to obtain crack-initiation threshold. Interface fracture toughness of zinc coating/304 stainless steel was obtained. A FEM was employed to verify the accuracy of acoustic emission method. The relationship between crack spacing and the film thickness was obtained. Effects of different parameters on the interface bonding strength were analyzed. Abstract: The three-point bending tests were carried out on zinc coating/304 stainless steel with different film thicknesses by means of a universal testing device equipped with an acoustic emission technique to obtain crack-initiation threshold and interface fracture toughness. Tensile test was used to obtain the relationship between crack spacing and the film thickness. Then, the critical fracture toughness and the interface shear stress were studied and utilized to evaluate the mechanical properties of interface layer. At last, a finite element method (FEM) was employed to verify the accuracy of acoustic emission method by the comparison of results between experiment and FEM analysis. Both interface crack propagation length and stress phase angle were analyzed. The results illustrate that the propagation length of interface crack increases with increasing film thickness and external load. However, it decreases with the increase of the interface fracture toughness and the elastic modulus of the film. The stress phase angle at the crack tip declines as the elastic modulus of the film increases. With uniform condition, the interface crack length and stress phase angle change little when the Poisson's ratio increases.